Flexible Carbon-Based Nanogenerators. Issue 1782 (2015) - Deng, Ning-Qin; Tian, He; Xue, Qing-Tang; Wang, Zhe; Zhao, Hai-Ming; Ma, Shuo; Mi, Wen-Tian; Mohammad, Mohammad Ali; Yang, Yi; Ren, Tian-Ling
ABSTRACT: Nanogenerators (NGs) have great potential to solve the problems of energy depletion and environmental pollution. Here, two types of flexible nanogenerators (FNGs) based on graphene oxide (GO) and multiwall carbon nanotubes (MW-CNTs) are presented. The peak output voltage and current of GO based FNG reached up to 2 V and 30 nA, respectively, under 15 N force at 1 Hz. Moreover, the output voltage could be improved to 34.4 V when the frequency was increased to 10 Hz. It was also found the output voltage increased from 0.1 V to 2.0 V using a released GO structure. The other FNG was made by MW-CNTs mixed with ZnO nanoparticles (NPs). Its output voltage and power reached up to 7.5 V and 18.75 mW, respectively, which is much larger than that of bare ZnO based FNG. Furthermore, a peak voltage of 30 V could be gained by stamping one's foot on the FNG. Finally, a modified NG was fabricated using four springs and two flexible layers. As a result, the voltage and power reached up to 9 V and 27mW, respectively. These works may bring out broad applications in energy harvesting.